2016
DOI: 10.1038/mp.2015.205
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the genetic overlap between BMI and cognitive function

Abstract: Obesity and low cognitive function are associated with multiple adverse health outcomes across the life course. They have a small phenotypic correlation (r=−0.11; high body mass index (BMI)−low cognitive function), but whether they have a shared genetic aetiology is unknown. We investigated the phenotypic and genetic correlations between the traits using data from 6815 unrelated, genotyped members of Generation Scotland, an ethnically homogeneous cohort from five sites across Scotland. Genetic correlations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 40 publications
7
47
0
Order By: Relevance
“…This is in accordance with recent molecular genetics evidence that 75% of obesity related genes express preferentially in the brain (4). Similarly, the genetic correlation between cognition and BMI uncovered in our sample is at the same magnitude as molecular estimates of associations between more specific cognitive measures and BMI (15,18). The current evidence further supports the brain-gene association with obesity vulnerability.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with recent molecular genetics evidence that 75% of obesity related genes express preferentially in the brain (4). Similarly, the genetic correlation between cognition and BMI uncovered in our sample is at the same magnitude as molecular estimates of associations between more specific cognitive measures and BMI (15,18). The current evidence further supports the brain-gene association with obesity vulnerability.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly to other recent papers, (20,27), we used the weights of each individual feature within a neurobehavioural factor (personality test, cognitive test, brain parcel) to create an aggregate BMI risk score or poly-phenotype score (PPS). This is similar to the polygenic score approach in genetics, where the small effects of several polymorphisms are aggregated to yield a total effect score (15,19,20,27). We used the correlation values as weights to multiply each participant's scaled measurements, and aggregated the results into a single composite variable, the PPS.…”
Section: Creating Poly-phenotype Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…3b; Supplementary Table 5). Sixteen of the 22 cell types were also enriched "intelligence" and "worry", two traits genetically anticorrelated with obesity (overlapping sets of associated loci with opposite effect sizes) 27,28 ( Supplementary Table 7).…”
Section: A Distributed Set Of Neuronal Cell Types Enrich For Obesity mentioning
confidence: 99%
“…However, a direct causality from high BMI to impaired CF has not been supported by genetic studies, as indicated by findings of seven common genetic variants for both traits and a large genetic correlation (r=-0.51); [16]. With such a strong genetic predisposition for both BMI and impaired CF, the relation of BMI to CF might have been misconceptualized as causal and thus difficult to be consistent in the findings.…”
Section: Introductionmentioning
confidence: 99%